2013
DOI: 10.1002/imhj.21412
|View full text |Cite
|
Sign up to set email alerts
|

Social Withdrawal Behavior in Infancy: A History of the Concept and a Review of Published Studies Using the Alarm Distress Baby Scale

Abstract: This article reviews the studies using or validating the Alarm Distress Baby Scale (ADBB; A. Guedeney & J. Fermanian, 2001) within different countries, different populations, and different settings. After a brief summary of the theoretical backgrounds of infant social behavior, the results of the main controlled and methodologically comparable studies are summarized and discussed. Second, the results of some observational studies as well as different models of factor analysis are presented. The modified, five-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 60 publications
2
81
1
2
Order By: Relevance
“…11 For the CIB Scale, each of the 42 items was rated from 1 (a little) to 5 (a lot) and grouped into 5 composites. In addition, according to the infant's age, 26 specific infant items based on Brazelton's Neonatal Behavioral Assessment Scale 13 were rated and grouped into 2 additional composites (see Methods section in the Supplemental Information).…”
Section: Blind Evaluation Of Social Skillsmentioning
confidence: 99%
“…11 For the CIB Scale, each of the 42 items was rated from 1 (a little) to 5 (a lot) and grouped into 5 composites. In addition, according to the infant's age, 26 specific infant items based on Brazelton's Neonatal Behavioral Assessment Scale 13 were rated and grouped into 2 additional composites (see Methods section in the Supplemental Information).…”
Section: Blind Evaluation Of Social Skillsmentioning
confidence: 99%
“…However, research indicates that risk of attachment disturbances may be possible to detect already during the first year of the child’s life. Infant social withdrawal indicates infant distress and it is suggested that this may be indicative of early attachment disturbances and it has been found to be a serious risk factor for infant mental health [21, 22]. Infant social withdrawal is seen by lack of either positive emotional expressions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…According to Dollberg, Feldman, Keren, and Guedeney [23] sustained withdrawal behavior in infants can be seen as a more chronic diminishing of the attachment system, which over time may develop in to a generalized persistent pattern of lowered engagement and reactivity to the environment. In more European countries the use of the validated systematic screening method, Alarm Distress Baby Scale (ADBB) [24] for identifying infant delayed socio-emotional development in infant mental health clinics and in home visiting programs have shown promising results [22, 25, 26]. …”
Section: Introductionmentioning
confidence: 99%
“…Novamente, a maior parte destas avaliações publicadas foi realizada durante consultas de rotina pediátrica ou de puericultura, tomando por base o comportamento do bebê em relação a um profissional de saúde estranho a ele. Em menor número, alguns trabalhos analisaram o retraimento na interação entre o bebê e sua mãe, por meio de filmagens posteriormente codificadas por profissionais devidamente treinados, assim como foi realizado no presente estudo (Puura et al, 2013;Burtchen et al;2013;Dollberg et Keren, 2013;Dollberg et al, 2006).…”
Section: Desenvolvimento Psíquico Dos Bebês: Uma Perspectiva Bidireciunclassified
“…Julia Durand). Em outros estudos, a ADBB já havia sido aplicada, com resultados satisfatórios, a filmagens de momentos de interação entre os bebês e suas mães (Dollberg et al, 2006;Puura et al, 2007;Puura et al, 2013;Burtchen et al, 2013).…”
Section: Treinamento E Aplicação Da Adbb No Contexto Do Estudounclassified